2012
DOI: 10.1093/ejcts/ezs080
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory complications after oesophagectomy for cancer do not affect disease-free survival

Abstract: When postoperative mortality is excluded, postoperative complications do not affect DFS in patients with complete resection. This deserves substantial information regarding the prognosis of subgroup of patients in critical situations where incrementing intensive care is debated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(59 citation statements)
references
References 21 publications
6
51
2
Order By: Relevance
“…These results agree with D'Annoville et al, who found that technical complications were associated with worse immediate hospital outcomes, but did not affect longterm survival 8 . In addition, major postoperative morbidities were found to significantly increase patient LOS.…”
Section: Discussionsupporting
confidence: 92%
“…These results agree with D'Annoville et al, who found that technical complications were associated with worse immediate hospital outcomes, but did not affect longterm survival 8 . In addition, major postoperative morbidities were found to significantly increase patient LOS.…”
Section: Discussionsupporting
confidence: 92%
“…One study found that Japanese patients with postoperative complications had worse prognoses than those without complications, 9 whereas other studies have found no independent effect of surgical complications on patient survival. [12][13][14][15] However, these studies were limited by small sample sizes and low statistical power. Because of the publication bias that results in small studies with ''significant'' results having a much higher likelihood of being published than small studies with null results, the importance of large-scale studies cannot be emphasized strongly enough.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, presenting the potential risk factors associated with pulmonary complications ensures the anticipation of complications by determining preventive strategies. In previous studies, for specific surgical groups, like upper abdominal interventions (4), oesophagectomy (5), total knee arthroplasty (6) or coronary artery bypass surgery (7), preoperative risk factors in the development of PPCs were investigated. The European Society of Anaesthesiology (ESA) performed a multinational, multicentre study called PERISCOPE (Prospective Evaluation of a Risk Score for postoperative pulmonary Complications in Europe), which our clinic also attended.…”
Section: Introductionmentioning
confidence: 99%